NCS-1 Deficiency Affects mRNA Levels of Genes Involved in Regulation of ATP Synthesis and Mitochondrial Stress in Highly Vulnerable Substantia nigra Dopaminergic Neurons - Simons, Carsten; Benkert, Julia; Deuter, Nora; Poetschke, Christina; Pongs, Olaf; Schneider, Toni; Duda, Johanna; Liss, Birgit (Frontiers in Molecular Neuroscience, 2019)
Neuronal Ca2+ sensor proteins (NCS) transduce changes in Ca2+ homeostasis into altered signaling and neuronal function. NCS-1 activity has emerged as important for neuronal viability and pathophysiology. The progressive degeneration of DA neurons, particularly within the Substantia nigra (SN), is the hallmark of Parkinson’s disease (PD), causing its motor-symptoms. The activity-related Ca2+ homeostasis of SN DA neurons, mitochondrial dysfunction, and metabolic stress promote neurodegeneration and PD. In contrast, NCS-1 in general has neuroprotective effects. The underlying mechanisms are unclear. We analyzed transcriptional changes in SN DA neurons upon NCS-1 loss by combining laser-microdissection and RT-qPCR-approaches to compare expression-levels of a panel of PD and/or Ca2+-stress related genes from wildtype and NCS-1 KO mice. In NCS-1 KO, we detected significantly lower mRNA-levels of mitochondrially coded ND1, a subunit of the respiratory chain, and of the neuron-specific enolase ENO2, a glycolytic enzyme. We also detected lower levels of the mitochondrial uncoupling proteins UCP4 and UCP5, the PARK7 gene-product DJ-1, and the Ca2+ channel Cav2.3 in SN DA neurons from NCS-1 KO. Transcripts of other analyzed UCPs, mitochondrial Ca2+ transporters, PARK-genes, and ion channels were not altered. As Cav channels are linked to regulation of gene-expression, metabolic stress and degeneration of SN DA neurons in PD, we analyzed Cav2.3 KO mice, to address if the transcriptional changes in NCS-1 KO were also present in Cav.2.3 KO, and thus probably correlated with lower Cav2.3-transcripts. However, in SN DA neurons from Cav2.3 KO mice, ND1 mRNA- as well as genomic DNA-levels were elevated, while ENO2, UCP4, UCP5 and DJ-1 transcript-levels were not altered. In conclusion, our data indicate a possible novel function of NCS-1 in regulating gene-transcription or stabilization of mRNAs in SN DA neurons. Although we do not provide functional data, our findings at the transcript level could point to impaired ATP-production (lower ND1 and ENO2) and elevated metabolic stress (lower UCP4, UCP5, and DJ-1 levels) in SN DA neurons from NCS-1 KO. We speculate that NCS-1 is involved in stimulating ATP-synthesis, while at the same time controlling mitochondrial metabolic stress, and in this way could protect SN DA neurons from degeneration.